PENGARUH BRAND PERSONALITY TERHADAP PURCHASE DECISION SMARTPHONE DIMEDIASI BRAND TRUST - Halim, Sherliana; Maulana, Nugraha; Hidayanti, Ayuk; Batu, Reminta Lumban (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
Smartphones have now become something that cannot be separated in daily activities for the lives of many people around the world. With the development of this technology, the smartphone industry continues to grow and experience intense competition. Companies must build and manage brands through Brand Personality because brands are one of the intangible assets for companies that have an important role as the basis of the company's competitive advantage. Consumer confidence in a product will increase when the company has a strong brand personality. The existence of consumer confidence will increase consumer purchasing decisions for a product. The purpose of this study was to determine how much influence brand personality has on Samsung smartphone purchasing decisions mediated by the brand trust variable. The sample in this study amounted to 110 respondents from Samsung smartphone users. The method used in this research is descriptive and verification methods. This study uses a simple random sampling technique using the formula Hair et al. This study uses two types of data, namely primary data and secondary data. Data processing uses path analysis with Statistics software Version 21 and LISREL 9.30 for students. The results of this study prove that there is a positive and significant influence of brand personality on Samsung smartphone purchasing decisions mediated by brand trust.